Techniques to widen the operational space of SPIDER Radio Frequency driven plasma source. Issue 1 (1st April 2022) - Casagrande, R; Dan, M; Maistrello, A
Abstract: SPIDER is the full-size prototype of the ion source of the ITER Neutral Beam Injectors, and is in operation since June 2018 as part of the ITER Neutral Beam Test Facility. The ion source is composed of 8 Radio Frequency drivers supplied by 4 RF oscillators, rated for operation at 1 MHz, for a total power of 800kW. This article presents a strategy for the selection of source biasing and of operating frequencies of the different RF generators to facilitate plasma initiation and to improve plasma stability. This operational strategy improved the plant reliability at high RF power in a broader range of operational conditions in SPIDER.